Fear of Missing Out dan Social Media Addiction: Study Meta Analisis - Ida Ayu Nyoman Kartikawati; Seto Mulyadi; Wahyu Rahardjo (Humanitas (Jurnal Psikologi), 2024)
In this era of globalization, the internet network has become a major factor in carrying out daily life such as for communication, accessing information, education, entertainment, social, business and government. An easily accessible internet network can provide the need to be connected and curiosity quickly, potentially giving rise to problematic internet usage behavior (PIU) and feelings of fear missing out and being left behind on information or events (FOMO). Research related to the relationship between FOMO and PIU has been widely conducted, therefore it is necessary to know the effect size of the results of previous studies as a reference for further research related to FOMO and PIU. This study looked at 19 international publication articles from 2019-2024. The results of the random effect size showed a moderate effect size (r = 0.461; z = 12.368 p = <0.001; 95% CLI [0.388; 0.534]). This finding suggests that Fear of Missing Out can be a predictor of problematic internet use. Problematic internet use occurs because individuals with a fear of missing out are driven to relieve feelings of worry and anxiety due to fear of missing out on important information or events that make them feel like they are being left behind. The results of the analysis also noted that there is potential to investigate moderator variables FOMO with PIU.